Eradication of biofilms on tympanostomy tubes with acetic acid treatment: an in vitro study. Issue 6 (4th May 2020) - Kjeldsen, Mathilde; Homøe, Preben; Kirstine Nielsen, Anne; Crone, Stephanie; Nørskov Kragh, Kasper; Bjarnsholt, Thomas
Abstract : The purpose was to evaluate the eradicative effect of acetic acid on bacterial biofilm grown on tympanostomy tubes by an in vitro experiment. Biofilms of Pseudomonas aeruginosa and Staphylococcus aureus were grown on sterile tympanostomy tubes for 24 h. The tubes were treated with acetic acid solutions at various concentrations for 24 h. Main outcome was viability of bacteria after treatment. The presence of consistently attached biofilm was examined on selected tympanostomy tubes with confocal laser scanning microscopy. Both pH‐adjusted and non‐pH‐adjusted media solutions were applied as control groups. Results showed complete eradication of P. aeruginosa biofilm with 0.50% v/v acetic acid. Biofilm of S. aureus was eradicated with 1.25% v/v acetic acid. Low pH value alone led to decreased growth of already established biofilm, but not eradication. In conlusion, acetic acid showed an eradicating effect on biofilm established on sterile tympanostomy tubes in vitro .